A comprehensive review on infant formula: nutritional and functional constituents, recent trends in processing and its impact on infants’ gut microbiota - Bakshi, Shiva; Paswan, Vinod Kumar; Yadav, Satya Prakash; Bhinchhar, Basant Kumar; Kharkwal, Sheela; Rose, Hency; Kanetkar, Prajasattak; Kumar, Vishal; Al-Zamani, Zakarya Ali Saleh; Bunkar, Durga Shankar (Frontiers in Nutrition, 2023)
Human milk is considered the most valuable form of nutrition for infants for their growth, development and function. So far, there are still some cases where feeding human milk is not feasible. As a result, the market for infant formula is widely increasing, and formula feeding become an alternative or substitute for breastfeeding. The nutritional value of the formula can be improved by adding functional bioactive compounds like probiotics, prebiotics, human milk oligosaccharides, vitamins, minerals, taurine, inositol, osteopontin, lactoferrin, gangliosides, carnitine etc. For processing of infant formula, diverse thermal and non-thermal technologies have been employed. Infant formula can be either in powdered form, which requires reconstitution with water or in ready-to-feed liquid form, among which powder form is readily available, shelf-stable and vastly marketed. Infants’ gut microbiota is a complex ecosystem and the nutrient composition of infant formula is recognised to have a lasting effect on it. Likewise, the gut microbiota establishment closely parallels with host immune development and growth. Therefore, it must be contemplated as an important factor for consideration while developing formulas. In this review, we have focused on the formulation and manufacturing of safe and nutritious infant formula equivalent to human milk or aligning with the infant’s needs and its ultimate impact on infants’ gut microbiota.